The encyclopedia of housing (Sage, 1998)
"Need to know how housing is financed? What is Situ construction? Need to define home matching? This encyclopedia provides access to a wealth of information drawn from many disciplines. With more than 500 entries, from abandonment to zoning, these capsules go beyond merely providing definitions of housing topics: they describe, elaborate, and critically assess issues of relevance to a wide variety of readers. Appendixes that cover major federal legislation and list major organizations and journals accompany the entries".--"Outstanding Reference Sources : the 1999 Selection of New Titles", American Libraries, May 1999. Comp. by the Reference Sources Committee, RUSA, ALA.